2009
DOI: 10.1063/1.3236544
|View full text |Cite
|
Sign up to set email alerts
|

Structural relaxation and crystallization of NiTi thin film metallic glasses

Abstract: Glass transition behavior, crystallization kinetics, and microstructure change of Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 bulk metallic glass under high pressure Effects of relaxation on glass transition and crystallization of ZrTiCuNiBe bulk metallic glass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 29 publications
2
6
0
2
Order By: Relevance
“…The absolute values of hardness and Young's moduli, e.g. Ti 50 Ni 40 Cu 10 ∼3.7 GPa and 115 GPa, respectively, correspond well to values published for other Ti-Ni thin films determined using nanoindentation [53][54][55][56][57]. However, the Young's moduli for the martensite are considerably larger than those determined for bulk alloys, for which additionally, the Young's modulus of austenite is found to be larger than that of martensite, i.e.…”
Section: Resultssupporting
confidence: 86%
“…The absolute values of hardness and Young's moduli, e.g. Ti 50 Ni 40 Cu 10 ∼3.7 GPa and 115 GPa, respectively, correspond well to values published for other Ti-Ni thin films determined using nanoindentation [53][54][55][56][57]. However, the Young's moduli for the martensite are considerably larger than those determined for bulk alloys, for which additionally, the Young's modulus of austenite is found to be larger than that of martensite, i.e.…”
Section: Resultssupporting
confidence: 86%
“…This may be due to the stress relaxation of the films after the heating process. 50 Surface analysis using X-ray photoelectron spectroscopy Surface structure and chemical composition of the implanted materials have crucial roles in their function and performance in biological conditions. Therefore, surface chemistry of fabricated metallic glass thin films was investigated.…”
Section: Patterning Of Ticuni Thin Films By the Thermal Imprinting Tementioning
confidence: 99%
“…This is largely due to the technical difficulty in characterizing the structural features of an amorphous matrix. It has been reported that heating at low temperatures (e.g., 400 C) increases the Young's modulus and hardness of NiTi amorphous thin films, and both effects are attributed to the reduction of free volume in the matrix associated with relaxation caused by heating [17]. It has also been reported that the crystallization nucleation rate is increased after a pre-relaxation treatment, leading to a more homogeneous grain size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is attributed to the formation of short-range ordered clusters during structural relaxation, which favor nucleation. However, it is not clear how the short-range ordered clusters are formed by atomic rearrangement [17]. Peterlechner et al [13] studied the relaxation of cold rolled NiTi containing amorphous and highly deformed crystalline domains by means of modulated DSC measurements.…”
Section: Introductionmentioning
confidence: 99%